ECF Recommendations for healthier and safer streets after the coronavirus pandemic. - Panozzo, Niccolò; Kabell, Morten (My University, 2020)
Epidemiological studies on what hinders and what facilitates the spread of Coronavirus, have already shown a clear correlation between air pollution and the way COVID-19 circulates and affects people. The European Cyclists’ Federation has released recommendations for safer streets. These include making cycling safe and convenient, using speed limit reductions and providing subsidy schemes for purchasing bikes.
Keywords: Verkehrssicherheit; Fahrradverkehr; Luftverschmutzung; Luftverbesserung; Fahrbahnmarkierung; Corona-Krise; Städtisches Leben; Fahrradinfrastruktur